Electron Impact Excitation of Singly Charged Indium Ion (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
We study electron impact excitation of In\({}^{+}\) using relativistic distorted wave method and report cross sections for 37 transitions among the fine-structure levels of \(5s^2\), \(5s5p\), \(5s5d\), \(5s6s\) and \(5s6p\) configurations at the scattered electron energies upto 200 eV.  The bound state wavefunctions of the target ion are obtained within multi-configuration Dirac-Fock approach. Our calculated oscillator strengths are compared with the results from the NIST database and other theoretical calculations. Cross sections are fitted with an analytical formula and the fitting parameters are made available for their possible applications in plasma modeling.
Keywords: Relativistic distorted waves; Multiconfiguration Dirac-Fock method; Dipole allowed transition; Cross sections; Oscillator strength; Fitting parametres